کسبِ رزق کے سلسلے میں قرآن کریم کی منفرد تعلیمات: The unique teachings of the Holy Quran in relation to livelihood - Shoaib Siddique; Zahoor Elahi; Hafiz Samama Tahir (International Research Journal of Arabic and Islamic Studies, 2024)
Adoption of livelihood is a very important issue. Its importance is also clear from this statement of Allah Almighty "And seek the grace of Allah, and remember Allah often so that you may be successful." In Surah Al-Juma'ah, Allah, the Exalted, commands to find sustenance after performing the great duty of Jumu'ah: “So spread over the earth and seek the grace of Allah.” In the matter of earning livelihood, Allah Almighty and Rasulullah ﷺ did not leave the mankind in shock, but the reasons for earning sustenance have been clearly explained in the Quran and Sunnah, if humanity understands these reasons well, understand and hold fast to them and make use of them in the best manner, then Allah, the Lord of the Mulk, who is "the Sustainer of the Mighty, the Mighty", will open the doors of sustenance for the people from all sides - send down goodness and blessings from the sky and the earth, shower many blessings. Similarly, there are twenty proofs in the Holy Qur'an and the blessed Hadiths that indicate the merits and importance of earning livelihood.